Hyperbolic Metamaterials via Hierarchical Block Copolymer Nanostructures (Advanced Optical Materials 7/2021). Issue 7 (6th April 2021) - Murataj, Irdi; Channab, Marwan; Cara, Eleonora; Pirri, Candido F.; Boarino, Luca; Angelini, Angelo; Ferrarese Lupi, Federico
Abstract : The dewetting of lamellar phase block copolymer films over topographically defined substrates generates hierarchically aligned hyperbolic metamaterials (HMM) with in‐plane optical axis. Strong reduction in the fluorescence lifetime was observed in nanodiamonds coupled to the Au/air HMM. The analyzed system exhibits hyperbolic behavior in a broad wavelength range in the visible spectrum. For further details, see article number 2001933 by Federico Ferrarese Lupi and co‐workers.